Knowledge management framework using green IT to implement sustainable entrepreneur ecosystem - Uddin, Mueen; Hindu, Roop Chand; Alsaqour, Raed A.; Shah , Asadullah; Abubakar, Adamu; Saba, Tanzila (Natural Publishing, 2015)
A strategy of ecosystem and green computing practices to develop a sustainable entrepreneur ecosystem is at once at obliging and baffling pretend to growing enterprises. This strategy must be studied thoroughly to create a concern among stakeholders and dealing with composite impact of their practicalities on the ecosystem. The finding presented in this paper explore specific sustainability issues being confronted by stakeholders throughout globe to implement sustainable entrepreneur ecosystem by using echo-friendly techniques and practices. We highlight a deep and thorough analysis of different gainsays confronted by top business enterprises within the area of a knowledge management framework using green IT techniques, and show how framework is targeted for specific goals. The suggested framework conceives the relationship between ecosystem and green IT to develop a sustainable entrepreneur ecosystem. The proposed framework includes the related models that will help to develop a conceptual framework for sustainable entrepreneur ecosystem.